(3cfR GdMbGFb aj cTa GdObGFbs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eMeO GdHQgjei GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdebOS HLdGd CdhgjJg Yf eSGQM GdChgGe CeG HYO aEf ceGd GdCfaS GdEfSGfjI EfeG jMUd eG dG MGWI HGdeYbhdGJ hGdYde HGdeLghdGJ aYdi GdYGbd GdSYi ai JMUjd CcedgG hGdEMGWI HCaVdgG s
(3BNQgG (B:s
(3hHgG JfGd GdSdGeI ai GdYGLdI hGdSYGOI ddBLdI agPG BNQ eG TQMfG ZaQ Gddg dg hdhGdOjI hdLejY GdeSdjf Bejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B114s
Keywords: (3GdJUha hGdBOGH GdTQYjIs